2014
DOI: 10.1186/1471-2261-14-182
|View full text |Cite
|
Sign up to set email alerts
|

Implication of plasma intermedin levels in patients who underwent first-time diagnostic coronary angiography: a single centre, cross-sectional study

Abstract: BackgroundIntermedin (IMD) is involved in the prevention of atherosclerotic plaque progression, possessing cardioprotective effects from hypertrophy, fibrosis and ischemia-reperfusion injury. Elevated plasma IMD levels have been demonstrated in patients with acute coronary syndromes. No human study has examined the role of IMD in stable patients who underwent diagnostic coronary angiography with suspicion of coronary artery disease (CAD). Thus we investigated the role of IMD as a biomarker to discriminate pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…After cardiac muscle has been affected by pathological factors, substances such as endocrine TGF-β, Ang II, and endothelin directly stimulate the proliferation of fibroblasts and the production of collagen [18,21]. Ang II can inhibit the synthesis of myocardial cells and secretion of IMD1-53, and exogenous IMD1-53 significantly inhibits Ang II induction of the proliferation of cardiac fibroblasts [12,22]. This study found that the gene expression of TGF-β was significantly decreased with IMD1-53, and smad3 phosphorylation levels were significantly decreased, suggesting that the anti-fibrosis effect of IMD1-53 is realized by inhibiting TGF-β expression so as to block smad3 phosphorylation, while the IMD CRLR did not change significantly, indicating that IMD1-53 inhibition of myocardial fibrosis may not related to the number of receptors.…”
Section: Discussionmentioning
confidence: 99%
“…After cardiac muscle has been affected by pathological factors, substances such as endocrine TGF-β, Ang II, and endothelin directly stimulate the proliferation of fibroblasts and the production of collagen [18,21]. Ang II can inhibit the synthesis of myocardial cells and secretion of IMD1-53, and exogenous IMD1-53 significantly inhibits Ang II induction of the proliferation of cardiac fibroblasts [12,22]. This study found that the gene expression of TGF-β was significantly decreased with IMD1-53, and smad3 phosphorylation levels were significantly decreased, suggesting that the anti-fibrosis effect of IMD1-53 is realized by inhibiting TGF-β expression so as to block smad3 phosphorylation, while the IMD CRLR did not change significantly, indicating that IMD1-53 inhibition of myocardial fibrosis may not related to the number of receptors.…”
Section: Discussionmentioning
confidence: 99%